Analisis Moda Transportasi Distribusi Komoditas Hasil Laut (Studi Kasus Pelabuhan PPI Kota Parepare) - Edil; Hakzah; Andriyani (Fakultas Teknik Universitas Muhammadiyah Parepare, 2026)
Efficient transportation is essential for maintaining the quality of marine fishery products and supporting seafood distribution activities. Therefore, understanding the characteristics of transportation modes used in the distribution process is important for improving logistics performance. This study aims to analyze the characteristics of seafood commodity distribution, identify distribution destinations, and examine the relationship between travel distance and travel time of transportation modes operating at the Cempae Fish Landing Base or PPI Cempae, Parepare City, Indonesia. Data were collected from 200 respondents through surveys and interviews and analyzed using descriptive statistics and simple linear regression. The results showed that motorcycles and pickup trucks were the primary transportation modes used in seafood distribution, accounting for 72% and 28%, respectively. Fish were the dominant commodity distributed to markets within and outside Parepare City. Regression analysis produced the equations y = 0.042 + 0.189x for pickup trucks and y = 0.049 + 0.285x for motorcycles, indicating a positive relationship between travel distance and travel time.